Changes in cardiovascular-health blood biomarkers in response to exercise intervention among older adults with cognitive frailty: A scoping review - Ibrahim, Azianah; Mat Ludin, Arimi Fitri; Singh, Devinder Kaur Ajit; Rajab, Nor Fadilah; Shahar, Suzana (Frontiers in Physiology, 2023)
INTRODUCTION: Cardiovascular health contributes significantly to the incidence of cognitive impairment. Prior to conducting exercise-related intervention, it is crucial to explore cardiovascular health blood parameters that have been commonly used as a guidance for the purpose of monitoring. Information on effectiveness of exercise on cardiovascular-related biomarkers are lacking, especially among older adults with cognitive frailty. Therefore, we aimed to review the existing evidence on cardiovascular-related blood parameters and their changes following exercise intervention among older adults with cognitive frailty. METHODS: Systematic search was conducted on Pubmed, Cochrane and Scopus databases. Related studies involving only human, full text in either English or Malay language were selected. Types of impairment were limited to cognitive impairment, frailty, and cognitive frailty. Studies were restricted to randomised controlled trial and clinical trial design studies. Trends in types of parameters studied were explored. RESULTS: A total of 607 articles were screened and final 16 were included in this review. Four cardiovascular related blood parameters categories were extracted: inflammatory, glucose homeostasis, lipid profile and haemostatic biomarkers. The common parameters that were monitored were IGF-1 and in some studies with HbA1c, glucose and insulin sensitivity. Out of the nine studies with inflammatory biomarkers, exercise interventions showed reduction in pro-inflammatory markers, namely IL-6, TNF-α, IL-15, Leptin and C-Reactive protein, and increase in anti-inflammatory markers of IFN-γ and IL10. Similarly, in all eight studies, glucose homeostasis-related biomarkers had improved with exercise intervention. Lipid profile was tested in five studies, with four studies showing improvements with exercise via decrease in TC, TG and LDL, and increase in HDL. Decrease in pro-inflammatory and increase in anti-inflammatory biomarkers were demonstrated with multicomponent exercise, including aerobic in six studies and in the remaining two, with aerobic exercise on its own. Meanwhile, four out of six studies which yielded improvements in glucose homeostasis biomarkers involved only aerobic exercise and another two studies involved multicomponent with aerobic exercise. CONCLUSION: The most consistent blood parameters studied were glucose homeostasis and inflammatory biomarkers. These parameters have been shown to improve with multicomponent exercise programmes, particularly with inclusion of aerobic exercise.